(untitled) (Economic and Political Thought, 2014)
The basic aim of the article is to systemise the typology of common goods. The concept of common goods, although in use for a long time and researched into a number of times, is not interpreted unequivocally. Researchers prefer analysing the mechanisms of particular common goods to looking for common basis for defining common goods described in literature. Moreover, the conducted analysis of the phenomenon places common goods in the classic goods classification, gives an insight into additional criteria narrowing the concept of the common good, and creates the basis for formulating a dynamic definition of the common good according to the level of the good saturation with features thought to be the key ones for the concept.